Impact of hydrothermal treatment on chemical composition and quality parameters of mushroom products - Bobel (Zinchenko), Inna; Terletska, Vita (My University, 2013)
The optimum mode of hydrothermal treatment of Pleurotus Ostreatus and Agaricus bisporus mushrooms has been determined. The impact of hydrothermal treatment on the changes of the activity of polyphenol oxidase, protein substances and carbohydrates losses of ready-to-cook mushroom foods were tested. It has been discovered that with the introduction of salt and citric acid in the solution the amount of protein losses has decreased in Pleurotus Ostreatus by 5.0-29.5 %, Agaricus bisporus – 5.7-19.0 %. Визначено оптимальний режим гідротермічної обробки грибів Pleurotus Ostreatus та Agaricus bisporus. Було досліджено вплив гідротермічної обробки на зміни активності поліфенолоксидази, втрати білкових речовин та вуглеводів у готових до приготування грибних стравах. Встановлено, що з введенням солі та лимонної кислоти в розчин втрати білка зменшилися у Pleurotus Ostreatus на 5,0-29,5%, Agaricus bisporus – на 5,7-19,0%.
Keywords: chips; snacks; глива звичайна; печериця двоспорова; чіпси; снеки; кафедра технології хлібопекарських і кондитерських виробів